Reflections on an official proposal for second language teaching materials - Lozada Trimbath, Minnie (2013)
Peruvian educational authorities have been implementing a bilingual intercultural program for several decades in our country. one of the various actions they have under taken is concerned with the preparation of materials for the teaching of spanish as a second language. the objective of this study is to find out what the leading ideas of this material are with respect to methodological approach and teaching strategies. the study will also allow us to reflect on the relationship between materials and educational reality, particularly having in mind the characteristics of students and the development of teachers and the contexts in which they are immersed.